CONTRIBUTION OF POLAND INTO COMPETITIVENESS OF EUROPE ON THE GLOBAL MARKET OF BUSINESS TOURISM - Wróblewski, Sławomir (Acta Scientiarum Polonorum. Oeconomia, 2010)
For the last few years, statistic data concerning international conferences and congresses, which constitute the crucial component of the business tourism, show gradual, single digit but systematic, declining trend in the share of Europe as business destination in the scale of the global market. According to ICCA annual reports, a little bit more then 50% of all international meetings are located in Europe, however, a gradual decrease in this share is being observed. One of the threats to the still dominating position of Europe, is an increased popularity of Asian destinations, including China. Counteracting this trend was one of main objectives of European Federation of Associations of Professional Congress Organisers EFAPCO, established in 2005. Since its inception, Poland is being represented in EFAPCO. The Polish Conference and Congress Association PCCA has been a founder member, and the Pole is acting for two terms as the EFAPCO First Vice-President. The organization and the field of tourism business is an interesting example of the contribution of Poles to building the position of Europe on the global market. The paper is showing the issue relating to trends of the development of this sector in Poland.